ANALYSIS OF THE IMPLEMENTATION OF E-PARTICIPATION IN PUBLIC POLICY IN INDONESIA: POTENTIAL, CHALLENGES AND IMPACT ON THE QUALITY OF PUBLIC POLICY - Yanto, Pebri; Jumanah, Jumanah; Sutoto, Sutoto (Universitas Nasional, 2024)
Abstract This study was conducted to analyze the implementation of E-participation in public policy in Indonesia with a focus on the potential, challenges, and impacts on the quality of public policy. E-participation as a policy-making process that involves public participation facilitated by digital technology has been implemented through various platforms such as LAPOR! and E-Musrenbang. This study uses a systematic literature review method of previous studies published between 2014 and 2024 to conduct the analysis. The results of the study indicate that although there has been an increase in the number of public participation through digital platforms, the effectiveness and impact of E-participation are still limited. The main challenges of implementing E-participation include unequal internet access, low levels of digital literacy, and bureaucratic resistance. In addition, coordination between government agencies in managing the E-participation platform is also a significant obstacle. Although E-participation has great potential to increase transparency, accountability, and inclusiveness of public policy, the improvement of policy quality has not been optimal due to the lack of follow-up to public input. To maximize the potential of E-participation, it is necessary to improve digital infrastructure, strengthen digital literacy, and develop more effective and transparent feedback mechanisms in managing public participation. Abstrak Penelitian ini dilakukan untuk melakukan analisis terhadap implementasi E-participation dalam kebijakan publik di Indonesia dengan fokus pada potensi, tantangan, serta dampaknya terhadap kualitas kebijakan publik. E-participation sebagai proses pembuatan kebijakan yang melibatkan partisipasi masyarakat dengan difasilitasi oleh teknologi digital telah diimplementasikan melalui berbagai platform seperti LAPOR! dan E-Musrenbang. Penelitian ini menggunakan metode literature review sistematis terhadap studi terdahulu yang telah diterbitkan antara tahun 2014 hingga 2024 untuk melakukan analisis. Hasil penelitian menunjukkan, meskipun terjadi peningkatan dalam jumlah partisipasi masyarakat melalui platform digital, efektivitas dan dampak E-participation masih terbatas. Tantangan utama implementasi E-participation meliputi ketidakmerataan akses internet, rendahnya tingkat literasi digital, dan resistensi birokrasi. Selain itu, koordinasi antarinstansi pemerintah dalam mengelola platform E-participation juga menjadi kendala yang signifikan. Meskipun E-participation memiliki potensi besar untuk meningkatkan transparansi, akuntabilitas, dan inklusivitas kebijakan publik, peningkatan kualitas kebijakan belum optimal karena kurangnya tindak lanjut terhadap masukan masyarakat. Untuk memaksimalkan potensi E-participation, diperlukan peningkatan infrastruktur digital, penguatan literasi digital, serta pengembangan mekanisme umpan balik yang lebih efektif dan transparan dalam pengelolaan partisipasi masyarakat.